A study on the laptop air cooling system - Chan, Darren (2015)
The effectiveness and efficiency of the laptop air cooling systems have to be improved as the modern day computing power play catch-up. The objective of this project is to develop and conduct a comprehensive experiment, in order to better understand the mechanics of the conventional air-cooling system in a typical 60mm x 60mm x 6mm laptop air cooling system. The test-rig of this project was built upon the previous and designed to be modular such that it encompasses flexibility to support a greater variety of experiments. Evaluation of the prototype by the previous FYP student was conducted and it suggested that there was no significant improvement in the performance of the cooling system with the integration of the aero foils. An attempt to increase the flow rate of the system by increasing pump power revealed the sensitivity of the compact flow channel towards the reduction of the flow outlet area. A reduction in 50% of the flow outlet area resulted in a 57% drop in flow rate. Further studies were conducted to understand the effects in which the mean flow rate and pressure difference had on the effectiveness of cooling. Experimental results showed that a leak-proof cooling system design performed much better than one without a leak-proof design. Also, the flow rate of the system should be optimized rather than maximized as the increase in mean flow rather after a certain point do not bring about a proportionate increase in heat transfer, which would prove to be insignificant in ameliorating computer performance. The convective heat transfer coefficient was also identified to be a key parameter in the design of a laptop air cooling system.